Perencanaan Bak Penampungan Air yang Berasal Dari Mata Air di Lingkungan Universitas Jambi - Fiqroh Muhamad Akbar; Ade Nurdin; M Nuklirullah (Jurnal Talenta Sipil, 2022)
Jambi University is one of the State Universities in Indonesia which is currently in the phase of sustainable development which is currently focusing on increasing development, especially water resource infrastructure. Planning for water reservoirs with reinforced concrete is an option in long-term infrastructure planning. The planned reservoir is in the form of a reservoir that functions as a container for storing clean water in the water treatment system at the Jambi University. Planning focuses on the design of the capacity and structural elements of the reinforced concrete reservoir. Planning refers to ACI-350M using the LRFD method, as well as SNI 7509:2011. The reservoir capacity is planned according to (Al-Layla et al., 1977)at 39% of the maximum water discharge, and the structural elements of the reservoir are planned in the form of beams, columns, upper, lower plates and walls. Based on the design, the reservoir capacity is 216 m3 with a length of 12 m, a width of 6 m and a height of 3.5 m. In planning the structural elements used concrete quality 21 MPa with the type of reinforcement BJTP-28. Based on the design results, the column size is 20 cm x 20 cm with 4D12 reinforcement details, then for beam sizes 30 cm x 20 cm using 4D12 for tensile reinforcement and 3D12 for compression reinforcement, and for plates using a thickness of 150 cm with reinforcement details D12-150 for top plate and D12-200 for bottom plate and wall plate.